Athabasca oil sands region snow contains efficient micron and nano-sized ice nucleating particles. (September 2019) - Rangel-Alvarado, Rodrigo B.; Willis, Chelsea E.; Kirk, Jane L.; St Louis, Vincent L.; Amyot, Marc; Bélanger, Dominic; Ariya, Parisa A.
Abstract: The Athabasca Oil Sands Region (AOSR) in Alberta, Canada, is an important source of atmospheric pollutants, such as aerosols, that have repercussions on both the climate and human health. We show that the mean freezing temperature of snow-borne particles from AOSR was elevated (−7.1 ± 1.8 °C), higher than mineral dust which freezes at ∼ −15 °C and is recognized as one of the most relevant ice nuclei globally. Ice nucleation of nanosized snow samples indicated an elevated freezing ability (−11.6 ± 2.0 °C), which was statistically much higher than snow-borne particles from downtown Montreal. AOSR snow had a higher concentration (∼2 orders of magnitude) of >100 nm particles than Montreal. Triple quadrupole ICP-(QQQ)-MS/MS analysis of AOSR and Montreal snow demonstrated that most concentrations of metals, including those identified as emerging nanoparticulate contaminants, were much more elevated in AOSR in contrast to Montreal: 34.1, 34.1, 16.6, 5.8, 0.3, 0.1, and 9.4 mg/m 3 for Cr, Ni, Cu, As, Se, Cd, and Pb respectively, in AOSR and 1.3, 0.3, 2.0, <0.03, 0.1, 0.03, and 1.2 mg/m 3 in Montreal snow. High-resolution Scanning Transmission Electron Microscopy/Energy-dispersive X-ray Spectroscopy (STEM-EDS) imaging provided evidence for various anthropogenic nano-materials, including carbon nanotubes resembling structures, in AOSR snow up to 7–25 km away from major oil sands upgrading facilities. In summary, particles characterized as coming from oil sands are more efficient at ice nucleation. We discuss the potential impacts of AOSR emissions on atmospheric and microphysical processes (ice nucleation and precipitation) both locally and regionally. Graphical abstract: Image 1 Highlights: Oil sands snow has much higher concentrations of particulate matter than snow from the urban areas. Some snow-borne particles near oil sands are very efficient ice nucleating particles. Coatings can create a small crystallographic lattice mismatch resulting in increased ice nucleation efficiency. Efficient ice nucleating particles in clouds alter precipitation frequency, intensity and lifetimes of atmospheric pollutants. Abstract : Snow-borne particles near oil sands are very efficient ice nucleating particles which may signify an alteration of precipitation frequency and intensity in nearby areas.